Molecular recognition and binding of beta‐lactamase II from Bacillus cereus with penicillin V and sulbactam by spectroscopic analysis in combination with docking simulation. (10th February 2017) - Zhang, Yeli; Qiao, Pan; Li, Shuaihua; Feng, Xuan; Bian, Liujiao
Abstract: The molecular recognition and binding interaction of beta‐lactamase II from Bacillus cereus (Bc II) with penicillin V (PV) and sulbactam (Sul) at 277 K were studied by spectroscopic analysis and molecular docking. The results showed that a non‐fluorescence static complex was separately formed between Bc II and two ligands, the molecular ratio of Bc II to PV or Sul was both 1:1 in the binding and the binding constants were 2.00 × 10 6 and 3.98 × 10 5 (L/mol), respectively. The negative free energy changes and apparent activation energies indicated that both the binding processes were spontaneous. Molecular docking showed that in the binding process, the whole Sul molecule entered into the binding pocket of Bc II while only part of the whole PV molecule entered into the pocket due to a long side chain, and electrostatic interactions were the major contribution to the binding processes. In addition, a weak conformational change of Bc II was also observed in the molecular recognition and binding process of Bc II with PV or Sul. This study may provide some valuable information for exploring the recognition and binding of proteins with ligands in the binding process and for the design of novel super‐antibiotics.